For the first time Ecuador experiments the programming of a public televition - Coronel Salas, G. (2016)
© 2016 AISTI.In Ecuador there is an issue that is particularly important in the media context. In 2007, with the arrival of Rafael Correa to the presidency of the government it leads to the creation of a public television medium, a project that allows citizens have an area of public service. On the other hand, in 2013, a new Organic Law of Communication which is included for the first time the concept of public media is approved. In this research contextualizing the audiovisual landscape and some results of the genres that are present within the channel programming grid it is offered.